Effect of Ca2+ site substitution on structural, optical, electrical and magnetic properties in Nd3+ and Mn2+-co-doped calcium molybdato-tungstates. Issue 1 (1st January 2023) - Sawicki, B.; Tomaszewicz, E.; Guzik, M.; Groń, T.; Oboz, M.; Duda, H.; Pawlus, S.; Urbanowicz, P.
Abstract: Ca1-3x-y Mny []x Nd2x (MoO4 )1-3x (WO4 )3x molybdato-tungstates (▯ denotes vacant sites) were successfully synthesized by high-temperature solid-state reaction. New materials crystallize in scheelite-type structure within whole homogeneity range of solid solution ( x ≤ 0.2000 and y = 0.0200). Morphological features and particle size distribution were investigated by SEM and laser diffraction methods, respectively. Spectroscopic measurements in the UV–vis range was carried out to determine optical direct band gap ( E g ), Urbach energy ( E U ) and confirmation of structural disorder. Refractive index ( n ) was calculated using four different models. Magnetic studies revealed paramagnetic behavior with long-range ferrimagnetic and short-range antiferromagnetic interactions. New materials showed weak n -type electrical conductivity and thermoelectric power factor (S 2 σ) that strongly depends on Nd 3+ ions content. Dielectric parameters, i.e. relative permittivity (ε r ) and energy loss ( tanδ ) are insignificantly dependent on Nd 3+ ions concentration. These effects were considered in terms of structural defects, thermal activation of charge carriers, and the Maxwell–Wagner polarization.